Prevalence of sequelae related to post-COVID-19 syndrome: An integrative review of the literature (Research, Society and Development, 2024)
In the face of the COVID-19 pandemic, millions of people were infected around the world with the acute development of the disease, and, since then, evidence about possible chronic post-contagion effects has emerged in academia, leading to the advent of the term ‘post-COVID-19 syndrome’. In view of this, in the present work, the available evidence for investigating complications arising from COVID-19 infection is analyzed through an integrative literature review, aiming to describe and identify the main sequelae exposed. Fifity-six articles were included from the database on the PubMed platform using the descriptors: “post-acute COVID-19-19 syndrome” and “epidemiology”. The global prevalence of long COVID-19 ranged between 4.7% and 80%. The main risk factors described were advanced age, female sex, severity of the acute infection and previous respiratory disease. As for the most encountered symptoms, fatigue, dyspnea, cognitive dysfunction, and sleep disorders stand out. Long COVID-19 can manifest itself in multiple organ systems, the underlying pathophysiological events still require clarification. Furthermore, there is still no accepted standardized definition for post-COVID-19- syndrome, limiting the comparison of outcomes presented in different epidemiological studies.